Emergency Surgery during COVID-19: Lessons Learned - Bhattacharjee, Hemanga K.; Chaliyadan, Shafneed; Verma, Eshan; Kumaran, Keerthi; Bhargava, Priyank; Singh, Abhishek; Maitra, Souvik; Parshad, Rajinder (The Surgery Journal, 2020)
Introduction The ongoing coronavirus disease-2019 (COVID-19) pandemic has disrupted health services throughout the world. It has brought in several new challenges to deal with surgical emergencies. Herein, we report two suspected cases of COVID-19 that were operated during this “lockdown” period and highlight the protocols we followed and lessons we learned from this situation.Result Two patients from “red zones” for COVID-19 pandemic presented with acute abdomen, one a 64-year male, who presented with perforation peritonitis and another, a 57-year male with acute intestinal obstruction due to sigmoid volvulus. They also had associated COVID-19 symptoms. COVID-19 test could not be done at the time of their presentation to the hospital. Patients underwent emergency exploratory laparotomy assuming them to be positive for the infection. Surgical team was donned with full coverall personal protective equipment. Sudden and uncontrolled egression intraperitoneal free gas was avoided, Echelon flex 60 staplers were used to resect the volvulus without allowing the gas from the volvulus to escape; mesocolon was divided using vascular reload of the stapler, no electrosurgical devices were used to avoid the aerosolization of viral particles. Colostomy was done in both the patients. Both the patients turned out to be negative for COVID-19 subsequently and discharged from hospital in stable condition.Conclusion Surgeons need to adapt to safely execute emergency surgical procedures during this period of COVID-19 pandemic. Preparedness is of paramount importance. Full precautionary measures should be taken when dealing with any suspected case.
Keywords: COVID-19; personal protective equipment; emergency surgical procedures; operation room